2014
DOI: 10.1002/ejhf.125
|View full text |Cite
|
Sign up to set email alerts
|

A nurse‐based strategy reduces heart failure morbidity in patients admitted for acute decompensated heart failure in Brazil: the HELEN‐II clinical trial

Abstract: Aims Home‐based interventions for heart failure (HF) patients might be particularly effective in middle‐income countries, where social, cultural, and economic constraints limit the effectiveness of HF treatment outside the hospital environment. Methods and results HELEN‐II was a randomized clinical trial conducted in Brazil designed to evaluate the clinical efficacy of a nurse‐based strategy, started after discharge following an acute decompensated HF (ADHF) admission. HELEN‐II compares the efficacy of home vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
93
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(101 citation statements)
references
References 38 publications
0
93
0
8
Order By: Relevance
“…[28] Therefore, hospitalizations due to preventable causes -such as treatment nonadherence -lead to worse prognoses, and multidisciplinary teams should be aware of this to enable implementation of follow-up measures during admission, telephone follow-up, [34] and other strategies, such as a house call shortly after hospital discharge. [35,36] A limitation of the study was that, simply because patients primary cause for admission was other than nonadherence, does not mean those patients were adherent. Also, the difficulty in identifying the cause of decompensation at the time of inclusion should be considered, although strategies have been used to minimize the possibility of bias.…”
Section: Published By Sciedu Pressmentioning
confidence: 99%
“…[28] Therefore, hospitalizations due to preventable causes -such as treatment nonadherence -lead to worse prognoses, and multidisciplinary teams should be aware of this to enable implementation of follow-up measures during admission, telephone follow-up, [34] and other strategies, such as a house call shortly after hospital discharge. [35,36] A limitation of the study was that, simply because patients primary cause for admission was other than nonadherence, does not mean those patients were adherent. Also, the difficulty in identifying the cause of decompensation at the time of inclusion should be considered, although strategies have been used to minimize the possibility of bias.…”
Section: Published By Sciedu Pressmentioning
confidence: 99%
“…A 6-month home and telephone follow-up study demonstrated a 27% relative reduction in the outcomes hospitalization, emergency care, or death. The study also improved HF knowledge and self-care actions 27 .…”
Section: Discussionmentioning
confidence: 77%
“…82,88 An intervention designed to improve problem-solving skills in patient and family dyads showed a positive effect on change in perceived control. 60 TPE interventions using direct 1-to-1 interactions did not reduce all-cause or cardiac mortality, 68,76,87,91 with the exception of a study by Dracup and colleagues 72 ; however, more studies showed a benefit of 1-to-1 TPE interventions Better attitude about dietary sodium intake at 6 wk (P=0.01)…”
Section: Hf Outcomesmentioning
confidence: 96%